Role of the BAHD1 Chromatin-Repressive Complex in Placental Development and Regulation of Steroid Metabolism. - Goran Lakisic; Alice Lebreton; Renaud Pourpre; Olivia Wendling; Emanuele Libertini; Elizabeth J Radford; Morwenna Le Guillou; Marie-France Champy; Marie Wattenhofer-Donzé; Guillaume Soubigou; Slimane Ait-Si-Ali; Jean Feunteun; et al. (PLoS Genetics)
BAHD1 is a vertebrate protein that promotes heterochromatin formation and gene repression in association with several epigenetic regulators. However, its physiological roles remain unknown. Here, we demonstrate that ablation of the Bahd1 gene results in hypocholesterolemia, hypoglycemia and decreased body fat in mice. It also causes placental growth restriction with a drop of trophoblast glycogen cells, a reduction of fetal weight and a high neonatal mortality rate. By intersecting transcriptome data from murine Bahd1 knockout (KO) placentas at stages E16.5 and E18.5 of gestation, Bahd1-KO embryonic fibroblasts, and human cells stably expressing BAHD1, we also show that changes in BAHD1 levels alter expression of steroid/lipid metabolism genes. Biochemical analysis of the BAHD1-associated multiprotein complex identifies MIER proteins as novel partners of BAHD1 and suggests that BAHD1-MIER interaction forms a hub for histone deacetylases and methyltransferases, chromatin readers and transcription factors. We further show that overexpression of BAHD1 leads to an increase of MIER1 enrichment on the inactive X chromosome (Xi). In addition, BAHD1 and MIER1/3 repress expression of the steroid hormone receptor genes ESR1 and PGR, both playing important roles in placental development and energy metabolism. Moreover, modulation of BAHD1 expression in HEK293 cells triggers epigenetic changes at the ESR1 locus. Together, these results identify BAHD1 as a core component of a chromatin-repressive complex regulating placental morphogenesis and body fat storage and suggest that its dysfunction may contribute to several human diseases.